Study the Changes in (pH, Turbidity, Hardness, and Total Organic Carbon) Levels of Water using Plant Membrane (Palm Leaves Powder) and Aquatic Plant System (Vine Stems) - Maaroof, Ahmed A.; Sharif, Fryad M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
Due to the increasing industrialization and urbanization, the requirement of clean water has been growing quite fast and it has the potential to keep increasing. There are many regions facing water crisis even some countries with a rich water source. In this study, three types of water (tap, ground, and light sewage) have been collected from different places in Ibrahim Ahmad site in Sulaymaniyah city/Kurdistan region – Iraq. The research studies the effects of plant membrane method, and aquatic plant system on the improvement of pH, turbidity, hardness, and total organic carbon (TOC) of water samples. In the plant membrane, palm leaves were crushed and used as a powder in filter bags; whereas in the aquatic plant system, vine stems were used by growing up the vines. The experimental results showed that the pH, hardness, turbidity, and TOC of water samples after using palm leaves powder and vine stems have been changed significantly with slight variation in some test results. The results of turbidity showed that using palm leaves powder as plant membrane was more effective than the vine stems in an aquatic plant system. On the other hand, the results of hardness and TOC tests of all water samples after using both methods proved that the vine stems method was more reliable than the palm leaves method. Finally, the pH results of all water samples after using both methods have been decreased to the normal range with a slight variation between the vine stems and palm leaves methods.